An Investigation of Request Types and Politeness Strategies among Senior High School EFL Learners - Nurhayati, Siti; Ariatmi, Siti Zuhriah (Journal of English Language and Education, 2025)
This research explores the types of requests and politeness strategies used by eleventh-grade students at SMA Muhammadiyah Program Khusus Surakarta in various social interactions. Employing a qualitative descriptive approach, data were collected through Discourse Completion Tasks (DCTs) featuring scenarios with teachers, peers, parents, and strangers. Analysis was conducted using Trosborg’s (1995) classification and Brown and Levinson’s (1987) politeness theory. Results reveal that conventionally indirect requests, particularly those expressing ability, willingness, or permission, are the most common. Both positive and negative politeness strategies frequently appeared, while bald-on-record forms were mostly used in urgent or familiar situations. These findings suggest that students demonstrate sensitivity to social context and power dynamics, reflecting the influence of the school’s character education in fostering polite and contextually appropriate communication in English